A new species of the genus Celaenorrhinus Hübner, [1819] from Hainan, China (Lepidoptera, Hesperiidae) - Li, Hua-Zhao; Liu, Zhe; Li, Jia-Ling (Zootaxa, 2024)
A new species, Celaenorrhinus qianhanae Li & Liu sp. nov., is described from Hainan, China. Its unique genital characteristics and wing markings are compared with other congeneric species from this island and adjacent regions, including Vietnam and China, etc. In addition, its COI gene is sequenced for molecular analysis, and the secondary sexual character, hair tufts on hind tibiae, is discussed for comparison.